Faktor Lokasi Usaha Terhadap Tingkat Pendapatan Industri Restoran Cepat Saji Di Kota Kupang - Maria Amingota Kewa Mangu; Muhammad Husain Hasan; Tugma Jaya Manalu (Universitas Negeri Gorontalo, 2025)
Fast food restaurants in Kupang City are in line with the changing lifestyles of the community, which are becoming more practical and modern. The purpose of this study is to analyze the business location factors that affect income levels, describe the income of fast food restaurants in Kupang City, and identify the restaurants with the highest income. The method used in this study is descriptive qualitative. The results of the study show that (1) business location factors that influence the income of fast food restaurants include: proximity to crowded areas, accessibility, level of competition, location rental costs, facilities and infrastructure, and environmental characteristics. (2) Restaurants located in the center of community activities with easy access and complete facilities earn higher incomes than restaurants in less strategic locations. Income differences are also influenced by business scale and brand strength. The average monthly income of local restaurants ranges from IDR 2,000,000 to IDR 20,000,000, while national and international franchise restaurants reach IDR 30,000,000 to IDR 300,000,000. (3) McDonald's Kupang is listed as the restaurant with the highest income due to its combination of strategic location, complete facilities, and high customer loyalty.